The Effect of Organizational Culture, Work-Life Balance, and Job Satisfaction on Non-Commercial Employee Work Engagement - Munawar, Ma’sum; Suriyanti , S. (Golden Ratio of Human Resource Management, 2024)
A person's attachment to their work (work engagement) is a view that is satisfying and provides positive motivation related to work results, which is characterized by a high level of enthusiasm and strong identification with one's work. Employees with high work engagement will be able to mobilize all their abilities for the progress and sustainability of the company. The problem formulation in this research is to determine the influence of Organizational Empowerment, Work Life Balance, and Job Satisfaction on the Work Engagement of Employees of the Non-Commercial Division of PT. Royalboard Banguninti Granito. Research data was taken using observation techniques and questionnaires using Google Form media, with a sample of 56 staff-up employees. The data analysis technique used is multiple linear regression analysis to prove the research hypothesis. Data that has met validity, reliability, and classical assumption tests is then processed to obtain a regression equation. Based on the results of this research, it can be concluded that there is a positive and significant influence of the variables Organizational Culture, Work Life Balance, and Job Satisfaction on Work Engagement among employees PT. Royalboard Banguninti Granito both simultaneously and partially.